Characterization of Rubisco Activase Genes in Maize: An α-Isoform Gene Functions alongside a β-Isoform Gene. Issue 4 (7th February 2014) - Yin, Zhitong; Zhang, Zhenliang; Deng, Dexiang; Chao, Maoni; Gao, Qingsong; Wang, Yijun; Yang, Zefeng; Bian, Yunlong; Hao, Derong; Xu, Chenwu
Abstract : An α-isoform Rubisco activase gene contributes to the synthesis of a large polypeptide in maize . Abstract: Rubisco activase (RCA) catalyzes the activation of Rubisco in vivo and plays a crucial role in regulating plant growth. In maize ( Zea mays ), only β-form RCA genes have been cloned and characterized. In this study, a genome-wide survey revealed the presence of an α-form RCA gene and a β-form RCA gene in the maize genome, herein referred to as ZmRCAα and ZmRCAβ, respectively. An analysis of genomic DNA and complementary DNA sequences suggested that alternative splicing of the ZmRCAβ precursor mRNA (premRNA) at its 3′ untranslated region could produce two distinctive ZmRCAβ transcripts. Analyses by electrophoresis and matrix-assisted laser desorption/ionization-tandem time-of-flight mass spectrometry showed that ZmRCAα and ZmRCAβ encode larger and smaller polypeptides of approximately 46 and 43 kD, respectively. Transcriptional analyses demonstrated that the expression levels of both ZmRCA α and ZmRCAβ were higher in leaves and during grain filling and that expression followed a specific cyclic day/night pattern. In 123 maize inbred lines with extensive genetic diversity, the transcript abundance and protein expression levels of these two RCA genes were positively correlated with grain yield. Additionally, both genes demonstrated a similar correlation with grain yield compared with three C4 photosynthesis genes. Our data suggest that, in addition to the β-form RCA-encoding gene, the α-form RCA-encoding gene also contributes to the synthesis of RCA in maize and support the hypothesis that RCA genes may play an important role in determining maize productivity.